Persistent Post-Root Canal Pain and Swelling in a 38-year-old Male - Mohit Kumar Kanoujia; Sumit Kumar; Khushboo Arif; Aman Rajput; S Deepak (Journal of Primary Care Dentistry and Oral Health)
Endodontic treatment, primarily root canal therapy, is a critical procedure to eliminate infection from the root canal system and prevent reinfection. This case report discusses the retreatment of a 38-year-old male patient who experienced persistent pain and swelling in the lower left molar region following root canal treatment. Clinical examination revealed tenderness, an exaggerated thermal response, and radiographic evidence of inadequate obturation with potential periapical inflammation. The retreatment involved careful removal of the previous obturation material, thorough cleaning and shaping of all canals to the correct working length, and final obturation extending to the apical terminus to ensure effective sealing. This case underscores the importance of precise root canal obturation, as underfilled root canals are a significant contributor to endodontic treatment failure. Successful outcomes in endodontics are highly dependent on correct working length determination and obturation quality, both of which prevent bacterial ingress. Studies corroborate that posterior teeth, particularly mandibular molars, are more susceptible to endodontic failures due to higher susceptibility to caries. This case emphasizes the need for continuous professional development in endodontic techniques to enhance treatment success rates. Proper root canal sealing is essential for the prognosis, and the use of advanced tools such as electronic apex locators, and Ni-Ti rotary instruments can optimize the accuracy of treatment.